University-industry collaboration: The impact of postdoctoral workstations on labor investment efficiency - Liu, Yiding; Yi, Kefu; Huang, Guanhua (Frontiers in Psychology, 2022)
This paper investigates whether managers use knowledge transferred from university-industry collaboration when making investment decisions on labor. To establish causality, we use a difference-in-difference method based on the staggered establishment of postdoctoral workstations in Chinese firms. We find that postdoctoral workstations enable managers to improve labor investment efficiency and thus help mitigate over- and under-investment problems in labor, and the higher the operational quality of the workstation, the more significant the increase in investment efficiency. This finding is robust to utilizing the event study approach, placebo test, propensity score matching, instrumental variable, and entropy balancing. Brain gain and knowledge transfer effects between universities and industries are two plausible mechanisms. Furthermore, the main effect is more pronounced for firms located closer to prestigious universities, firms are non-state-owned enterprises, human-capital-intensive, have political connections, and without national fellows’ lead. Our findings suggest that brain gain in firms does not merely increase or reduce labor investments Per se, but rather inspires managers to maintain optimal labor levels through knowledge transfer processes.